Autobiographical memories, identity disturbance and brain functioning in patients with borderline personality disorder: An fMRI study. Issue 3 (March 2019) - Bozzatello, Paola; Morese, Rosalba; Valentini, Maria Consuelo; Rocca, Paola; Bosco, Francesca; Bellino, Silvio
Abstract: Identity disturbance is a core feature of borderline personality disorder (BPD). Autobiographical memory is a process of reflective thinking through which we form links between elements of life and self. It can be considered as an indirect index of identity integration. The present study was aimed to investigate the differences in brain activity patterns between BPD patients with identity diffusion and healthy controls using fMRI. We enrolled 24 BPD patients and 24 healthy controls. Identity integration in patients and controls was assessed with the Identity Disturbance Questionnaire (IDQ) score and was significantly different (p = 0.001). We analysed hemodynamic response in the regions of interest during presentation of resolved and unresolved life events. With reference to the condition "resolved", increased cerebral activity in right anterior cingulate cortex (ACC), right medial prefrontal cortex (MPFC), right dorsolateral prefrontal cortex (DLPFC), and bilateral insula was registered in BPD patients compared with controls. In the condition "unresolved", increased brain activity was observed in patients in bilateral ACC, bilateral DLPFC, and right temporo-parietal junction. Hyperactivity in ACC and DLPFC in BPD patients with both conditions (resolved and unresolved contexts) may be due to an inefficient attempt to reconstruct a coherent narrative of life events (resolved or not).